Proceedings of the 3rd International Conference on Education Innovation (ICEI 2019) 2019
DOI: 10.2991/icei-19.2019.37
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Higher Education Leaders to Engage Research

Abstract: This study seeks to explore the role of the leadership of the college in cultivating research using a qualitative approach. The data collection methods used are interviews, observations, and document studies. Data analysis used is data condensation, data display, and data verification, while the validity test of the data used is the triangulation of source and engineering, and the member check. Results of this study showed that the role of the university leader in the study of research can be done by providing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…A qualitative study in Indonesia to explore the role of college leadership in cultivating research showed that the role of the university leader in research study can be played by providing funding support, spreading research information, motivating, retrieving appropriate policies related to the research activities of lecturers, establishing cooperation, facilitating civitas in research, and taking a humanistic approach [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study in Indonesia to explore the role of college leadership in cultivating research showed that the role of the university leader in research study can be played by providing funding support, spreading research information, motivating, retrieving appropriate policies related to the research activities of lecturers, establishing cooperation, facilitating civitas in research, and taking a humanistic approach [ 34 ].…”
Section: Discussionmentioning
confidence: 99%